2019
DOI: 10.1515/nanoph-2019-0328
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical impacts of AlGaN undershells on coaxial GaInN/GaN multiple-quantum-shells nanowires

Abstract: The superior crystalline quality of coaxial GaInN/GaN multiple-quantum shell (MQS) nanowires (NWs) was demonstrated by employing an AlGaN undershell during metal-organic chemical vapor deposition. Scanning transmission electron microscopy (STEM) results reveal that the NW structure consists of distinct GaInN/GaN regions on different positions of the NWs and the cores were dislocation-free. High-resolution atomic contrast STEM images verified the importance of AlGaN undershells in trapping the point defects dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…The addition of AlGaN underlayer (UL) on core-shell InGaN/GaN MQWs has recently been studied showing an improvement of IQE from 29 to 35%. 21,22 Also, Rishinaramangalam et al demonstrated a reduction of reverse leakage current on wires and triangular stripes covered with InGaN MQWs in presence of AlGaN UL. 23 A further optimized core-shell LED structure including AlGaN UL and electron blocking barrier (EBL) exhibiting an IQE as high as 62% have been reported by the group of Feezell with the demonstration wire-LED having an EQE equal to 8.3%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of AlGaN underlayer (UL) on core-shell InGaN/GaN MQWs has recently been studied showing an improvement of IQE from 29 to 35%. 21,22 Also, Rishinaramangalam et al demonstrated a reduction of reverse leakage current on wires and triangular stripes covered with InGaN MQWs in presence of AlGaN UL. 23 A further optimized core-shell LED structure including AlGaN UL and electron blocking barrier (EBL) exhibiting an IQE as high as 62% have been reported by the group of Feezell with the demonstration wire-LED having an EQE equal to 8.3%.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the additional AlGaN UL have been successfully integrated in core-shell InGaN QWs allowing to improve the IQE and EQE of wire-LEDs, as previously mentioned. 21,22,23,24 Hence, the objective of this work is to extend the UL study of m-plane core-shell InGaN MQW systems investigating the influence of GaN and low In-content InGaN pre-growth layers in order to improve the QW luminescence efficiency. The pre-growth of GaN layer aims to improve the crystal structural quality before the QW growth (GaN pre-layer is called "GaN spacer" hereafter).…”
Section: Introductionmentioning
confidence: 99%
“…However, up to now, the application of AlGaN as spacers within coaxial GaInN/GaN MQS nanowires has not yet been reported in the literature. Nevertheless, we preliminarily studied the effect of a thin AlGaN layer prior to the MQS structures growth, which showed an improvement in emission efficiency and reduction in the nonradiative recombination rate. , The structural and optical features of coaxial MQS nanowires demonstrated that the AlGaN undershell played an important role to suppress the diffusion of point defects from n -cores to MQS structures. Moreover, an n-type AlGaN undershell was used to suppress the contamination of silicon and oxygen impurities (from the SiN mask) in the p-GaN layer, which resulted in the reduction of reverse leakage current in coaxial nanowire LEDs .…”
Section: Introductionmentioning
confidence: 99%
“…These defects may be due to the low crystal quality of active layers on the c ‐plane of the NWs. [ 41–43 ]…”
Section: Resultsmentioning
confidence: 99%
“…These defects may be due to the low crystal quality of active layers on the c-plane of the NWs. [41][42][43] In region (ii), the defects originating from the m-plane of NW-MQS form on the basal plane (c-plane) and propagate along the m-axis direction, which is a lateral growth direction (indicated by region (ii) in Figure 5). Two types of defect contrasts are observed: defect contrasts that propagated to the coalescence region (indicated by z in Figure 5a) and those that terminate in the GaN layers (indicated by u in Figure 5a).…”
Section: Structural Evaluation and Defect Distribution Analysis Of Th...mentioning
confidence: 99%